Blueberry: A future super fruit - Negi, N D; Upadhyay, S K (Indian Horticulture, 2021)
Blueberries are increasing in popularity and are emerging as one of the most important small fruit crop in the world. The identification of antioxidant properties in blueberry fruit along with other health benefits has helped increase consumer demand. In most of the blueberry growing countries it is being grown on both small and large scale, on large scale most of the farms are mechanised in USA and Europe. It has been reported that blueberries have relatively less problem as compared to other crops so, once the plantation is established the maintenance cost is low. In India its production can be tried where soil is slight acidic and climate during winter remains cool enough to meet the chilling requirements. However, the southern blueberry cultivars which require relatively less chilling hours can also be tried in other parts of the country, provided availability of enough planting stock with technical knowledge to the growers. The initial studies at the Department of Horticulture, CSKHPKV, Palampur have shown quite encouraging results and the Department is working on its propagation and development of production technology.